Pengaruh Kemampuan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Pada CV Centra Moda Tanah Abang Jakarta Pusat : The Effect of Work Ability and Work Motivation on Employee Performance at CV Centra Moda in Tanah Abang, Central Jakarta - Ratna Septiniat Hura; Rani Rani (CV Warnak Johanna Nusantara, 2025)
This study aims to analyze the effect of work ability and work motivation on employee performance at CV Centra Moda Tanah Abang, Central Jakarta. The background of this research focuses on the role of employee performance to achieve company goals. Optimal performance is influenced by employee ability and motivation. The author emphasizes how important it is to create a supportive work environment to make employees feel more motivated and better at their jobs. Therefore, this study is expected to help management make better HR development strategies. Overall, this study provides important knowledge for management on how to make an effective approach to employee development; the focus of this study is to improve work ability and motivation to achieve the best level of performance. The population in this study consisted of 61 respondents, where the sample collection technique to be used in the following research is Non-Probability Sampling using saturated sampling.